The GlyR Extracellular β8–β9 Loop – A Functional Determinant of Agonist Potency - Janzen, Dieter; Schaefer, Natascha; Delto, Carolyn; Schindelin, Hermann; Villmann, Carmen (Frontiers in Molecular Neuroscience, 2017)
Ligand-binding of Cys-loop receptors results in rearrangements of extracellular loop structures which are further translated into the tilting of membrane spanning helices, and finally opening of the ion channels. The cryo-EM structure of the homopentameric 1 glycine receptor (GlyR) demonstrated an involvement of the extracellular β8-β9 loop in the transition from ligand-bound receptors to the open channel state. Recently, we identified a functional role of the β8-β9 loop in a novel startle disease mouse model shaky. The mutation of residue GlyRα1Q177 to lysine present in shaky mice resulted in reduced glycine potency, reduced synaptic expression, and a disrupted hydrogen network at the structural level around position GlyRα1Q177. Here, we investigated the role of amino acid volume, side chain length, and charge at position Q177 to get deeper insights into the functional role of the β8-β9 loop. We used a combined approach of in vitro expression analysis, functional electrophysiological recordings, and GlyR modeling to describe the role of Q177 for GlyR ion channel function. GlyRα1Q177 variants do not disturb ion channel transport to the cellular surface of transfected cells, neither in homomeric nor in heteromeric glycine receptor configurations. The EC50 values were increased for all GlyRα1Q177 variants in comparison to the wild type. The largest decrease in glycine potency was observed for the variant GlyRα1Q177R. Potencies of the partial agonists -alanine and taurine were also reduced. Our data are further supported by homology modeling. The GlyRα1Q177R variant does not form hydrogen bonds with the surrounding network of residue Q177 similar to the substitution with a basic lysine present in the mouse mutant shaky. Among all investigated Q177 mutants, the neutral exchange of glutamine to asparagine as well as the introduction of the closely related amino acid glutamic acid preserve the hydrogen bond network. Introduction of amino acids with small side chains or larger volume resulted in a loss of their hydrogen bonds to neighboring residues. The β8-β9 loop is thus an important structural and functional determinant of the inhibitory glycine receptor.